Q. 144.5( 21 Votes )

<span lang="EN-US

Answer :

Given that


Taking tan both sides, we get







(Since tan(tan-1A)=A)

4x+6x=1-24x2

24x2+10x-1=0

24x2+12x -2x -1=0

⇒12x(2x + 1) - 1(2x+1) = 0

(12x-1)(2x+1)=0

Hence

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers